Ectopic lipid metabolism in anterior pituitary dysfunction - Baumgartner, Clemens; Krššák, Martin; Vila, Greisa; Krebs, Michael; Wolf, Peter (Frontiers in Endocrinology, 2023)
Over the past decades, adapted lifestyle and dietary habits in industrialized countries have led to a progress of obesity and associated metabolic disorders. Concomitant insulin resistance and derangements in lipid metabolism foster the deposition of excess lipids in organs and tissues with limited capacity of physiologic lipid storage. In organs pivotal for systemic metabolic homeostasis, this ectopic lipid content disturbs metabolic action, thereby promotes the progression of metabolic disease, and inherits a risk for cardiometabolic complications. Pituitary hormone syndromes are commonly associated with metabolic diseases. However, the impact on subcutaneous, visceral, and ectopic fat stores between disorders and their underlying hormonal axes is rather different, and the underlying pathophysiological pathways remain largely unknown. Pituitary disorders might influence ectopic lipid deposition indirectly by modulating lipid metabolism and insulin sensitivity, but also directly by organ specific hormonal effects on energy metabolism. In this review, we aim to I) provide information about the impact of pituitary disorders on ectopic fat stores, II) and to present up-to-date knowledge on potential pathophysiological mechanisms of hormone action in ectopic lipid metabolism.